2011
DOI: 10.1111/j.1365-4632.2010.04799.x
|View full text |Cite
|
Sign up to set email alerts
|

CD26/dipeptidyl‐peptidase IV and adenosine deaminase serum levels in psoriatic patients treated with cyclosporine, etanercept, and psoralen plus ultraviolet A phototherapy

Abstract: The results show that ADA might be a useful marker indicating disease activity and T-cell activation. As significant changes were observed in serum CD26/DPP-IV before and after treatment, we think CD26/DPP-IV might play a role in psoriasis pathogenesis, which should be clarified by further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…These findings support the hypothesis that adenosine deaminase could be validated by further studies as a useful indicator in monitoring patients with psoriasis, assessing the response to therapy and predicting the prognosis of the disease (52,54,55). In previous studies on patients with psoriasis, adenosine deaminase activity was found to decline after treatment with PUVA, cyclosporine, etanercept, and psoralen, reconfirming the ability of this enzyme to be associated with T-cell activation (55,56). The increase in adenosine deaminase activity could become a predictive factor for identifying patients with psoriasis at risk of developing relapses prior to the occurrence of clinical manifestations.…”
Section: Psoriasis Vulgaris Pasi Score ------------------------------supporting
confidence: 71%
“…These findings support the hypothesis that adenosine deaminase could be validated by further studies as a useful indicator in monitoring patients with psoriasis, assessing the response to therapy and predicting the prognosis of the disease (52,54,55). In previous studies on patients with psoriasis, adenosine deaminase activity was found to decline after treatment with PUVA, cyclosporine, etanercept, and psoralen, reconfirming the ability of this enzyme to be associated with T-cell activation (55,56). The increase in adenosine deaminase activity could become a predictive factor for identifying patients with psoriasis at risk of developing relapses prior to the occurrence of clinical manifestations.…”
Section: Psoriasis Vulgaris Pasi Score ------------------------------supporting
confidence: 71%
“…Its mRNA, protein levels and activity are higher in psoriatic skin samples ( 245 , 246 ). By contrast, serum DPPIV levels and activity seem to be lower in patients ( 247 , 248 ), accompanied by a reduction of peripheral CD8 + CD26 + T cells ( 249 , 250 ). Two case reports suggest a link between the use of DPPIV inhibitor sitagliptin and psoriasis.…”
Section: The Dpp Family In Inflammatory Diseasementioning
confidence: 89%
“…Many studies have also reported a decrease of serum ADA levels after psoriasis treatment with different modalities including cyclosporine, etanercept, PUVA, and PTU. 10,22 On the contrary, one study found normal ADA activity in psoriatic patients. 23 This could be due to the few number of patients (only 18) and the use of a normal laboratory range instead of a control group in that study.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies report high ADA in the sera of psoriatic patients than that of the healthy controls. 21,22 Tikhonov et al 9 , found double activities of ADA and purine nucleoside phosphorylase (PNP) in the skin of psoriatic patients. In accordance with our results Hashemi et al 21 and Yildirum et al 22 found no correlation between serum ADA and PASI score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation